A high resolution analysis of 2v2/v2 +v4/2v4 bands of MGeH4 (M=76,74); High Resolution Molecular Spectroscopy, HRMS - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Koshelev M. A. Maksim Aleksandrovich; Velmuzhov A. P. Aleksandr Pavlovich; Velmuzhova I. A.; Sennikov P. G. Petr Gennadjevich (Poster Session H, 2015)
Title screen